2007
DOI: 10.1136/vr.161.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of commercial pig farms in Great Britain and their use of antimicrobials

Abstract: A mail survey of 1889 pig producers in Great Britain with more than 100 sows or more than 1000 pigs was carried out to investigate their use of antimicrobials and other health-related management practices. The response rate was 25.5 per cent. Antimicrobials were most commonly administered in feed. Depending on the production system, between 60 and 75 per cent of the farms had used antimicrobials in their weaner rations and 20 to 62 per cent had used them in their grower rations. Antimicrobial injections had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 3 publications
3
43
2
4
Order By: Relevance
“…Farmers also rated the risks of AMU and of AMR to be moderate. The latter finding seems to be in line with that of previous studies showing that farmers were neither very aware (Friedman and others 2007, Stevens and others 2007) nor very worried about AMR (Visschers and others 2015). In contrast to the benefits of AM, the risks of AMU are not directly noticeable to farmers as long as they do not experience therapeutic failure in their animals, themselves or the people living and working with them.…”
Section: Discussionsupporting
confidence: 92%
“…Farmers also rated the risks of AMU and of AMR to be moderate. The latter finding seems to be in line with that of previous studies showing that farmers were neither very aware (Friedman and others 2007, Stevens and others 2007) nor very worried about AMR (Visschers and others 2015). In contrast to the benefits of AM, the risks of AMU are not directly noticeable to farmers as long as they do not experience therapeutic failure in their animals, themselves or the people living and working with them.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Stevens and others (2007) found that 79 per cent of UK pig farmers considered ‘improved housing’ as an alternative to antimicrobial use. Participants considered the lack of profitability in the pig industry to limit their ability to improve housing, however, previous work shows that farms, where the farmer felt there was room for improvement in the farm environment, used more in-feed antimicrobials than those who did not (Scott and others 2006, 2007, Stevens and others 2007). This would inevitably increase drug costs on these farms.…”
Section: Discussionmentioning
confidence: 99%
“…This opinion was echoed in work by Stevens and others (2007) who showed that 96 per cent of pig farmers considered responsibility for ‘good practice in the use of antimicrobials’ to lie with vets. Busani and others (2004) defined a ‘judicious user’ of antimicrobials to be a cattle practitioner who showed an awareness of the problem of antimicrobial resistance and the importance of responsible use; three-quarters of cattle vets conformed to this description (Busani and others 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…▪ Farmers may see AM use as a tool that can be used to produce more and cheaper food (Stevens and others 2007) or to enhance performance parameters (Moreno 2014). …”
Section: The Problemmentioning
confidence: 99%